INTERPRETATION OF WILLIAM SHAKESPEARE'S “SONNET 18” THROUGH SEMANTIC ANALYSIS - Aidil Syah Putra; Audia Triana; Az Zahra Rizani (VARIABLE RESEARCH JOURNAL, 2024)
Poetry is a type of literary work in which the author expresses their feelings and message primarily through language. Poems employ words that have deeper, more nuanced meanings in addition to their literal ones. This is particularly true of William Shakespeare's "Sonnet 18," where certain words might be challenging to interpret. Thus, the purpose of this research is to apply semantic analysis, which focuses on lexical meaning and grammatical meaning, to assist poetry lovers in understanding the meaning of poetry. The words from fourteen lines of his poetry, which represent the fundamental degree of attention, serve as the research's data. The process of gathering data involves reading each word aloud several times. The descriptive qualitative research methodology was used in this study. This approach allows researchers to explore and understand phenomena in depth, explore meaning, and see the complexity of the subject under study. The result of this research is that the poetry Sonnet 18 by William Shakespeare tells the expression of admiration shown by the poet to someone he adored.